2004
DOI: 10.1111/j.0141-9838.2004.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation by malaria antigens renders mononuclear cells susceptible to HIV infection and re‐activates replication of endogenous HIV in cells from HIV‐infected adults

Abstract: We have tested the hypothesis that activation of T cells by exposure to malaria antigens facilitates both de novo HIV infection and viral reactivation and replication. PBMC from malaria-naive HIV-uninfected European donors could be productively infected with HIV following in vitro stimulation with a lysate of Plasmodium falciparum schizonts and PBMC from malaria-naive and malaria-exposed (semi-immune) HIV-positive adults were induced to produce higher levels of virus after stimulation with the same malaria ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…Additionally, a significant number (91.2%) had very weakened immunity (CD4 < 200) compared with 38.7% in HIV mono-infected patients. P. falciparum has been shown to stimulate HIV-1 replication through the production of cytokines (interleukin-6 and tumor necrosis factoralpha) by activated lymphocytes [15][16]. An important study from Malawi showed that HIV-1 plasma viral loads were significantly higher in patients with malaria infection than in those without, and these levels remained higher for up to 10 weeks after treatment [14], suggesting that malaria may speed the progression of HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a significant number (91.2%) had very weakened immunity (CD4 < 200) compared with 38.7% in HIV mono-infected patients. P. falciparum has been shown to stimulate HIV-1 replication through the production of cytokines (interleukin-6 and tumor necrosis factoralpha) by activated lymphocytes [15][16]. An important study from Malawi showed that HIV-1 plasma viral loads were significantly higher in patients with malaria infection than in those without, and these levels remained higher for up to 10 weeks after treatment [14], suggesting that malaria may speed the progression of HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is even worse in neonates, children, pregnant women, and immunocompromised individuals. Several studies have reported an enhanced susceptibility of HIV-infected individuals to various infections, including hepatitis, toxoplasmosis, pneumonia, malaria, and salmonellosis [1][2][3]. Similarly, prior infection with Helicobacter pylori infection enhances the susceptibility to infection with Salmonella typhi [4].…”
Section: Introductionmentioning
confidence: 99%
“…Acute malaria elevates the HIV viral load (VL), which in turn can enhance the risk for HIV transmission ). In addition, Plasmodium antigens lead to strong cellular activation (Worku et al 1997) which may facilitate de novo HIV-1 infection and replication (Froebel et al 2004). The preference of HIV-1 for infecting activated memory CD4 + T lymphocytes can increase cell death (Grossman et al 2002).…”
mentioning
confidence: 99%